Exploring khorezm tales abroad: a cross-cultural study (Genius Repository, 2023)
Khorezm tales, a rich collection of folk narratives from the Khorezm region of Central Asia, have long captivated the imagination of scholars and enthusiasts alike. These tales are a treasure trove of cultural heritage, offering insights into the history, beliefs, and values of the Khorezmian people. In recent years, there has been a growing interest in studying Khorezm tales abroad, as they provide a unique opportunity to explore the cultural diversity of Central Asia and promote cross-cultural understanding. This article delves into the significance of studying Khorezm tales abroad and examines the various approaches and methodologies employed by scholars in their research.